Los factores socio-políticos que conducen a la municipalidad de pueblo nuevo, a limitarse en los ámbitos de la responsabilidad social municipal en el año 2012. - Albarrán Leiva, Gianny Lizeth (2013)
In this investigation it has as function study the socio-political factors that they lead to the Municipality of New People to limit itself in the areas of the social municipal responsibility or which are described as consequences to the deficient labor ones of the own hard-working councillors and the municipality like institution not to allow the search and the joint and agreed by consensus work of interinstitutional strategies to link all the social and political actors in an interaction coordinated to solve the problems of the community. Likewise, is observed in this investigation that the deficient labors in the functions and roles and in the provision of services of the own hard-working councillors and the continuismo of the municipal local authorities generate the distrust of the citizens, which allows that the ethical image they should not have institutional representation. He appears besides the fact that the Municipality of New People in spite of realizing in his annual programmings the participative local budget, the population and his workers do not know that this one is a tool of the joint of the different social civil actors since are the neighbors, the private companies, and other political communal actors to strengthen to the community across the active and reliable participation in the implementation of social and economic projects.